Experience report: Products and interventions aimed at municipal Equity Committees in a health microregion of eastern Minas Gerais (Research, Society and Development, 2026)
The implementation of the principle of equity in the Unified Health System (SUS) requires strategies that combine diagnosis, planning, and intervention, especially at the municipal management level. The objective of this experience report was to share the methodology, results, and discussions of the tactical-operational phase of Situational Strategic Planning, based on the development of products and interventions directed at Equity Committees, with a view to strengthening these spaces. This is a qualitative and descriptive experience report developed in the context of the Education through Work for Health Program (PET-Saúde) – Equity, in the Eastern Macroregion of Minas Gerais. The experience refers to the actions of Tutorial Group 1, carried out in 16 municipalities in the Microregion of Governador Valadares. The situational diagnosis identified institutional resistance, insufficient training, and the absence of systematized tools for planning actions as the main challenges. Based on these findings, technical-pedagogical products were developed, including digital educational materials, a regulatory repository, interactive health education strategies, and a regional meeting with municipal representatives. The results indicated good acceptance of the products and potential for applicability in local contexts. It is concluded that the collective construction of technical and pedagogical products constitutes a powerful strategy for strengthening Equity Committees and promoting more inclusive and equitable practices in health work.